Ultrafast‐Response/Recovery Flexible Piezoresistive Sensors with DNA‐Like Double Helix Yarns for Epidermal Pulse Monitoring. Issue 2 (10th November 2021) - Chen, Jianming; Zhang, Jun; Hu, Jinlian; Luo, Ningqi; Sun, Fengxin; Venkatesan, Harun; Zhao, Ni; Zhang, Yuanting
Abstract: A key challenge in textile sensors is to adequately solve the hysteresis for more broad and exacting applications. Unlike the conventional strategy in integrating elastic polymers into the textile, the hysteretic issue is critically addressed here through the structural design of yarns to provide a twisting force. The underlying mechanism is fully discussed based on theory and modeling, which are in good agreement with experimental data. Impressively, the pressure sensor outperforms almost all reported textile‐based sensors in terms of recovery index, which refers to the ability to overcome the lagged deformation reflected by the hysteresis (5.3%) and relaxation time (2 ms). Besides, the sensor superiority is also demonstrated by way of its ultrafast response time (2 ms). Thanks to these merits, this pressure sensor is demonstrated to be capable of monitoring epidermal pulses and meanwhile shows great potential to advance the standardization and modernization of pulse palpation in traditional Chinese medicine. Abstract : Hysteresis is a critical issue existing in textiles sensors. Distinct from the conventional methods, in this work, a biomimetic DNA‐like double‐helix structure is introduced into a textile‐based pressure sensor, providing a twisting force to allow quick and sufficient recovery from the deformation. Ultimately, the hysteresis is largely inhibited together with an improved response/relaxation time.